Voices of Survival : A Qualitative Study On Childhood Trauma, Identity Fractures, and the Quest for Mental Health Validation - Jesynthia Wong, Robert; Nor Mazlina, Ghazali (International Journal of Environmental Science (IJES), 2025)
Psychological development and coping among adult survivors of childhood trauma provides important insight into the nature of childhood abuse, yet culturally situated of Malaysian survivors still remain underrepresented. In this qualitative study, the lived experiences of ten Malaysian young adults with childhood trauma are explored, by employing thematic analysis method, to understand how they are sense-making from their experiences. Four master themes emerged: (1) Erosion of Self (imposter syndrome, alienation), (2) Survival Coping (avoidance vs. adaptation), (3) Structural Betrayal (cost barriers, cultural incompetence), and (4) Trauma Minimization (comparative invalidation). Notably, participants described trauma as "an inherited language of pain"—shaping identity through internalized stigma and systemic abandonment. Findings challenge Western-centric trauma models by highlighting familial collectivism and religious taboos as unique barriers. Trauma-informed policies that center survivor voices in Malaysia’s mental health reform is to be argued for. This research positions survivors’ narratives not as peripheral stories, but as essential blueprints for decolonising trauma recovery in Malaysia and similar contexts.